A comparison of presentations and outcomes of histoplasmosis across patients with varying immune status. (13th January 2021) - Franklin, Alexander D; Larson, Lindsey; Rauseo, Adriana M; Rutjanawech, Sasinuch; Hendrix, Michael Joshua; Powderly, William G; Spec, Andrej
Abstract: Few large cohorts have examined histoplasmosis in both immunocompromised and immunocompetent patients. We describe the differences in presentations and outcomes of histoplasmosis by immune and dissemination status. We assembled a retrospective cohort of adult patients diagnosed with histoplasmosis from 2002 to 2017. Patients were grouped by immune status: people living with HIV (PLWH), patients who were HIV negative but had other-immunocompromise (OIC), and immunocompetent patients. Patients were further classified into asymptomatic lung nodule (ALN), localized and disseminated disease groups, and outcomes were compared across patients by these immune status categories We identified 261 patients with histoplasmosis: 54 (21%) PLWH, 98 (38%) OIC, and 109 (42%) immunocompetent. Disseminated disease was more common among PLWH than among other groups ( P < .001). In localized disease, median time from symptom onset to diagnosis was longer in immunocompetent patients than in other groups ( P = .012), and was not significant in disseminated disease. The 90-day mortality was higher in PLWH (25%) and OIC (26%) with localized disease compared to the immunocompetent group (4%) ( P = .009), but this difference was not seen in disseminated disease. Patients with localized disease had lower 90-day mortality (14%) compared to those with disseminated disease (21%) ( P = .034). We conclude that immunocompetent individuals present with fewer typical symptoms, laboratory findings, and radiographic features of Histoplasma infection, leading to potential delays in diagnosis in this group. Despite this, immunocompetent patients have lower 90-day mortality in localized disease, and do not experience increased 90-day mortality in disseminated disease. Lay Summary: This article examines how the signs and symptoms of histoplasmosis vary by immune status and dissemination status. Immunocompetent patients with localized disease present with fewer typical signs and symptoms, are diagnosed later, but despite this have lower 90-day mortality.